Numerical simulation of underground gas storage in an inclined aquifer - S. Mulyavin; J. Kolev; E. Mamchistova; A. Nasirova (Наука. Инновации. Технологии)
Introduction. Underground gas storage plays an important role in changing gas consumption. The main factors in the creation of UGS facilities are the presence of large gas consumers and the availability of the necessary reservoirs. The total volume of gas in UGS facilities is necessary to cover the needs of industrial enterprises and social needs both for short time periods (day, week) and for a longer period. Materials and methods of the research. Using the method of numerical modeling of the operation of underground gas storage, it becomes possible to substantiate the optimal parameters of its operation and control gas leaks from the storage. The results of the study and their discussion. Mathematical modeling of the cyclic operation of UGS facilities allows using the known pressure in the gas cavity to calculate the mass of gas in the underground storage, and thereby control gas leaks. Conclusions. The presented mathematical model of the operation of a linear underground gas storage in an aquifer, its numerical and software implementation makes it possible to construct hysteresis diagrams (P / Z, M) of UGS facilities for analyzing the operation of a gas storage facility, which are convenient for analyzing the operation of a storage facility and monitoring the parameters of its operation.